Antibacterial efficacy of quaternized chitosan/poly (vinyl alcohol) nanofiber membrane crosslinked with blocked diisocyanate. (15th June 2021) - Wu, Jheng-Yu; Ooi, Chien Wei; Song, Cher Pin; Wang, Chi-Yun; Liu, Bing-Lan; Lin, Guan-Yu; Chiu, Chen-Yaw; Chang, Yu-Kaung
Graphical abstract: Highlights: A hydrolysis-resistant nanofiber membrane (HTCC/PVA/BI) was prepared. Rapid thermal crosslinking of blocked diisocyanate improved the membrane stability. Antibacterial efficacy of HTCC/PVA/BI nanofiber membranes reached ∼100 %. Abstract: N -[(2-hydroxyl-3-trimethylammonium) propyl] chitosan chloride (HTCC), which is a type of chitosan derivative with quaternary ammonium groups, possesses a higher antibacterial activity as compared to the pristine chitosan. The nanofiber membranes made of HTCC are attractive for applications demanding for antibacterial function. However, the hydrophilic nature of HTCC makes it unsuitable for electrospinning of nanofibers. Hence, biodegradable polyvinyl alcohol (PVA) was proposed as an additive to improve the electrospinnability of HTCC. In this work, PVA/HTCC nanofiber membrane was crosslinked with the blocked diisocyanate (BI) to enhance the stability of nanofiber membrane in water. Microbiological assessments showed that the PVA/HTCC/BI nanofiber membranes possessed a good antibacterial efficacy (∼100 %) against E. coli . Moreover, the biocompatibility of PVA/HTCC/BI nanofiber membrane was proven by the cytotoxicity test on mouse fibroblasts. These promising results indicated that the PVA/HTCC/BI nanofiber membrane can be a promising material for food packaging and as a potential wound dressing for skin regeneration.